Hubungan Lama Menderita DM Dengan Kemampuan Mengingat Pada Lansia Di Desa Simorejo Kanor Bojonegoro - Zainal Abidin, Ahmad; Ali Yahya (PT. Pubsains Nur Cendekia, 2024)
Diabetes Mellitus (DM) is part of a form of degenerative disease which is still a special concern for the world of health, because it has its own frightening threat in society, so it is necessary to know the ability to remember in terms of a long time suffering from diabetes mellitus. The purpose of this study was to analyze the relationship between the duration of suffering from DM and the ability to remember the elderly in Simorejo Village, Kanor Bojonegoro. The research method used non-experimental with a cross sectional approach with a sample size of 65 from simple random sampling technique and using Kendall's tau_b statistical test with a confidence level of 95% (ᾳ=0.05). The results of this study obtained a p value using Kendall's tau_b correlation analysis of 0.000 which is less than ᾳ 0.05, which means that there is a significant relationship between the length of time suffering from DM and the ability to remember. The closeness value of the relationship in this study was 0.567, which means that the closeness is in the strong category. The conclusion in this study is that there is a significant relationship between the duration of suffering from DM and the ability to remember the elderly in Simorejo Village, Kanor Bojonegoro.